Evaluación de pan de molde con sustitución parcial de harina de trigo por harina de arroz de las variedades (Oryza rufipogon G., Oryza sativa L. spp. japonica, Oryza sativa L. spp.) - Arana Vaca, Kevin Antonio (2024)
Bread is one of the essential foods in the diet of Ecuadorians. However, domestic production of wheat flour is insufficient, forcing imports of this input and raising the price of the final product. In 2022, Ecuador imported close to 700 thousand tons of wheat, with an average annual expenditure of approximately $200 million dollars (Ministry of Agriculture and Livestock, 2020; Central Bank of Ecuador, 2023). In view of this situation, it is necessary to investigate alternatives to reduce the use of wheat flour without significantly compromising the characteristics and properties of bread. This study evaluates the effect of the partial substitution of wheat flour by rice flour of the varieties Oryza rufipogon G., Oryza sativa L. spp. japonica, Oryza sativa L. spp. on the physicochemical and organoleptic characteristics of bread. Parameters such as pH, moisture and ash content will be analyzed, as well as texture, flavor and general acceptability of the final product. The results of this study will contribute to the reduction of dependence on imported wheat flour, promoting the use of local ingredients and enhancing the economic sustainability of Ecuador's agroindustrial sector